Adverse childhood experiences are associated with illicit drug use among pregnant women with middle to high socioeconomic status: findings from the All Our Families Cohort - Cheryl L. Currie; Suzanne C. Tough (BMC, 2021)
Abstract Background Adverse childhood experiences (ACEs) are associated with illicit drug use among pregnant women who are socioeconomically vulnerable. While it is assumed that the impact of ACEs on illicit drug use in pregnancy is reduced among women with higher socioeconomic status (SES), this assumption is not well tested in the literature. The objective of this study was to examine the impact of maternal ACEs on illicit drug use in a community-based sample of pregnant women with middle to high SES. Methods This study is a secondary analysis of a prospective cohort study that collected data from 1660 women during and after pregnancy in Calgary, Canada between 2008 and 2011 using mailed surveys. Illicit drug use in pregnancy was self-reported by women at 34-36 weeks gestation. An established scale examined maternal ACEs before 18 years. Logistic regression models and 95% confidence intervals tested associations between maternal ACE scores and illicit drug use in pregnancy. Results Overall, 3.1% of women in this predominantly married, well-educated, middle and upper middle income sample reported illicit drug use in pregnancy. Women with 2-3 ACEs had more than a two-fold increase, and women with 4 or more ACEs had almost a four-fold increase in illicit drug use in pregnancy, relative to women with 0-1 ACEs after adjustment for confounders. Exposure to child abuse was more consistently associated with illicit drug use in pregnancy than exposure to household dysfunction in childhood. Conclusions Maternal ACEs were common and associated with a moderate increase in the odds of illicit drug use in pregnancy among Canadian women with middle to high SES.